Fatal Case of Crimean-Congo Hemorrhagic Fever, Portugal, 2024 - Líbia Zé-Zé; Cristina Nunes; Micaela Sousa; Rita de Sousa; Carla Gomes; Ana S. Santos; Rui T. Alexandre; Fátima Amaro; Tiago Loza; Miriam Blanco; Maria J. Alves (Emerging Infectious Diseases)
We report a fatal case of Crimean-Congo hemorrhagic fever in Portugal. An 83-year-old man, initially suspected of having Mediterranean spotted fever, was later confirmed to have Crimean-Congo hemorrhagic fever by the detection of viral genome in the patient's serum and the presence of specific IgM antibodies.